Nano hydrotalcite and aramid fiber / cross-linked copolymer composite leather finishing agent and preparation method thereof
Through the soapless emulsion cross-link polymerization technology and nanohydrotalcite and aramid fiber composite, the problems of insufficient weather resistance and mechanical strength of traditional polymer leather coating materials are solved, and efficient wear resistance and flame retardant performance are achieved. New environmentally friendly coating agents are provided.
Patent Information
- Application Number
- CN202411474766.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-22
AI Technical Summary
Traditional polymer leather coating materials have defects in weather resistance, mechanical strength and wear resistance, and cannot meet the functional and quality needs of high-end leather and its products.
The method of cross-linking and polymerization of soapless emulsions is used to combine nano-hydrotalcite and aramid fibers to form multi-crosslinked copolymers through hydrogen bonds, which improves the mechanical properties and wear resistance of the coating film, and improves water dispersion through interface synergistic action. and flame retardant properties.
It significantly improves the wear resistance, mechanical properties and flame retardant properties of the coating film, reduces stress concentration, and provides an environmentally friendly new nanocomposite leather finishing agent to enhance the hydrophobicity and thermal insulation of the product.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano composite materials, and specifically relates to a nano hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent and a preparation method thereof. Background Art
[0002] Leather finishing is a branch of the coating industry. It is a coating applied to the surface of leather products. Its main purpose is to beautify the appearance of leather, improve the performance and durability of leather products, etc. After a series of treatments and tanning stages, the raw leather must go through the finishing stage to truly become the leather products needed by the market. The changes in the styles of different leather products are also mainly achieved through the finishing process, and leather finishing agents play a key role. The traditional polymer leather finishing materials currently used in the industry mainly have defects such as poor mechanical properties and wear resistance, and cannot meet people's functional and quality requirements for high-end leather and its products. The use of nanomaterials and nanotechnology can significantly improve the poor weather resistance, low mechanical strength and wear resistance of traditional polymer coating materials. In this work, a multi-crosslinked copolymer coating emulsion was first prepared by the soap-free emulsion cross-linking polymerization method. The selected sodium p-styrene sulfonate monomer can not only participate in the polymerization as a functional monomer, but also play an emulsifying role, which greatly reduces the adverse effects of general emulsifiers on emulsion products. The synergistic coating effect of hydrotalcite two-dimensional nanosheets and one-dimensional aramid nanofibers can not only give the leather coating layer certain flame retardant, heat preservation and thermal stability properties, but also significantly improve the wear resistance of the polymer coating film. Summary of the invention
[0003] The present invention utilizes nanotechnology and new nanomaterials to improve traditional leather making technology, and aims to provide a nano-hydrotalcite@aramid fiber / cross-linked copolymer (LDH@NAF / H-PBMSA) composite leather finishing agent and a preparation method thereof. The one-dimensional nano-aramid fiber and the two-dimensional hydrotalcite nanosheet exert a synergistic finishing effect, and the interface synergistic effect after the two-dimensional hydrotalcite sheet and the aramid fiber are composited can improve the water dispersibility of the nano-composite particles. The nano-aramid fiber can form hydrogen bonds between polymer molecules to increase the physical cross-linking density and form a multi-cross-linked copolymer, thereby effectively improving the mechanical properties and wear resistance of the coating film.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent (LDH@NAF / H-PBMSA) comprises the following steps: (1) N-hydroxymethyl acrylamide (HAM), sodium bicarbonate (NaHCO3) and sodium p-styrene sulfonate (SSS) are dissolved in water, and then butyl acrylate (BA), methyl methacrylate (MMA) and acrylic acid (AA) are added for pre-emulsification to obtain pre-emulsified monomer I; butyl acrylate (BA), methyl methacrylate (MMA), sodium p-styrene sulfonate (SSS), acrylic acid (AA) are mixed with water for emulsification to obtain pre-emulsified monomer II; the pre-emulsified monomer I is heated to 40-50°C under stirring to obtain reaction solution ①, an initiator aqueous solution is added dropwise to the reaction solution ①, and then the temperature is increased to 75-85°C for reaction for 0.5-1 h to obtain reaction solution ②, and then the pre-emulsified monomer II and the remaining initiator aqueous solution are added dropwise to the reaction solution ② to continue the reaction for 4-7 h to obtain the target product cross-linked copolymer, which is recorded as H-PBMSA emulsion; (2) Under stirring, a mixed aqueous solution of zinc chloride (ZnCl2) and aluminum chloride (AlCl3) and an aqueous solution of sodium hydroxide (NaOH) were simultaneously added dropwise to the dispersion of nano-aramid fiber (NAF). After the addition was completed, the mixture was stirred at 75-85°C for 2-3 h, and then transferred to a hydrothermal reactor for hydrothermal reaction at 110-120°C for 10-20 h. The reaction was terminated and centrifuged. The solid product was washed and dried to obtain a nano-hydrotalcite@aramid fiber composite product, which was recorded as LDH@NAF and set aside. (3) Disperse LDH@NAF evenly in water to obtain dispersion A. Take H-PBMSA and adjust its pH to 7-8 under stirring. Add dispersion A dropwise into H-PBMSA and stir for 1-2 h to obtain nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent, recorded as LDH@NAF / H-PBMSA.
[0005] Furthermore, the preparation process of the dispersion of nano-aramid fiber (NAF) in step (2) is as follows: aramid is uniformly dispersed in dimethyl sulfoxide, followed by adding 0.05-0.2 g / mL potassium hydroxide aqueous solution, stirring and reacting at 30°C-50°C for 7-8 days, terminating the reaction, and adding deionized water and stirring for 1-2 h.
[0006] Preferably, 1 g of aramid needs to be dissolved in 400-600 mL of dimethyl sulfoxide, and 10-15 mL of 0.05-0.2 g / mL potassium hydroxide aqueous solution and 2000-3000 mL of deionized water need to be added to 1 g of aramid.
[0007] Furthermore, in the step (1), the molar ratio of each monomer in the pre-emulsified monomer I is: butyl acrylate: methyl methacrylate: sodium p-styrene sulfonate: acrylic acid: N-hydroxymethyl acrylamide = (33-34): (33-34): 1: (2-3): (3-4); the molar ratio of each monomer in the pre-emulsified monomer II is: butyl acrylate: methyl methacrylate: sodium p-styrene sulfonate: acrylic acid = (33-34): (33-34): 1: (2-3), and the amount of sodium bicarbonate added is 50-90% of the total molar amount of acrylic acid in the pre-emulsified monomer I and the pre-emulsified monomer II.
[0008] Furthermore, in the step (1), the total mass of the monomers of the pre-emulsified monomer I (the sum of the masses of butyl acrylate, methyl methacrylate, sodium p-styrene sulfonate, acrylic acid and N-hydroxymethyl acrylamide in the pre-emulsified monomer I) accounts for 33-35% of the total mass of the monomers added (the sum of the masses of butyl acrylate, methyl methacrylate, sodium p-styrene sulfonate, acrylic acid and N-hydroxymethyl acrylamide in the pre-emulsified monomer I and the sum of the masses of butyl acrylate, methyl methacrylate, sodium p-styrene sulfonate and acrylic acid in the pre-emulsified monomer II).
[0009] Furthermore, in the step (1), the initiator is ammonium persulfate (APS), the concentration of the initiator aqueous solution is 0.01-0.02 g / mL, the amount of the initiator (APS) added is 1-1.5% of the total mass of butyl acrylate, methyl methacrylate, acrylic acid monomer, N-hydroxymethyl acrylamide and sodium p-styrene sulfonate, wherein the amount of the initiator added to the pre-emulsified monomer I is 30-40% of the total amount of the initiator.
[0010] Furthermore, in the step (2), the molar ratio of zinc chloride, aluminum chloride and sodium hydroxide is 3:1:(9-12), the amount of nano-aramid fiber added is 3-4% of the total mass of zinc chloride and aluminum chloride, the concentration of zinc chloride in the mixed aqueous solution of zinc chloride and aluminum chloride is 0.2-0.3 mmol / mL, and the concentration of the sodium hydroxide aqueous solution is 0.8-1 mmol / mL.
[0011] Furthermore, in step (3), the amount of LDH@NAF added to the cross-linked copolymer matrix accounts for 0.1-2.5% of the effective amount of the polymer.
[0012] Furthermore, in step (3), ammonia water is used to adjust the pH to 7-8, and 0.004 g-0.100 g of LDH@NAF is dispersed in 5 mL of distilled water.
[0013] The multi-crosslinked copolymer is composed of soft segments and hard segments, and the mass ratio of the soft segments to the hard segments is (3-2): (2-1), and the HAM crosslinker accounts for 1-4% of the total mass of the polymer monomers. The soft segment is composed of butyl acrylate monomers, and the hard segment is composed of methyl methacrylate, acrylic acid and sodium p-styrene sulfonate monomers. Only when the ratio of the soft and hard segments is properly controlled can better film-forming properties be obtained.
[0014] The nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent is prepared by the preparation method.
[0015] The invention uses one-dimensional linear nano-aramid fiber and two-dimensional lamellar nano-hydrotalcite composite particles as reinforcing phases, N-hydroxymethyl acrylamide as a crosslinking agent, sodium p-styrene sulfonate as a reactive emulsifier and participates in copolymerization, and adopts a soap-free emulsion polymerization method to prepare a nano-hydrotalcite@aramid fiber / crosslinked copolymer composite leather finishing agent, which greatly reduces the influence of traditional emulsifiers on product performance. The prepared nano-composite leather finishing agent gives the finishing film good hydrophobicity, heat preservation and wear resistance, etc. The introduction of LDH@NAF composite nanoparticles not only significantly reduces the stress concentration phenomenon of the product material, but also gives the finishing film certain flame retardant properties. The invention provides a new idea and method for developing an environmentally friendly new nano-composite leather finishing agent. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Fourier transform infrared spectra of LDH, H-PBMSA (prepared in Example 1), and LDH@NAF / H-PBMSA (prepared in Example 6); Figure 2 In the figure: a is the UV-visible absorption spectra of four coating films of H-PBMSA (prepared in Example 1), LDH / H-PBMSA (prepared in Example 2), NAF / H-PBMSA (prepared in Example 3) and LDH@NAF / H-PBMSA (prepared in Example 6) at 250-800 nm, wherein illustrations ① to ④ correspond to the film-forming images of H-PBMSA, NAF / H-PBMSA, LDH / H-PBMSA and LDH@NAF / H-PBMSA on glass sheets, respectively; b is the UV-visible absorption spectra of LDH@NAF / H-PBMSA coating films prepared by adding different contents of LDH@NAF composite nanoparticles at 250-800 nm, wherein the illustrations correspond to the film-forming images of LDH@NAF added in an amount of 0 to 2.5% on glass sheets, respectively; Figure 3 Nano-hydrotalcite (a) and aramid fiber (b) observed under a scanning electron microscope (SEM), (c), (d) and (e) are the morphologies of LDH@NAF observed under different magnifications of SEM; Figure 4 In the figure: a is the thermogravimetric curve spectra (TG) of four coating films of H-PBMSA (prepared in Example 1), LDH / H-PBMSA (prepared in Example 2), NAF / H-PBMSA (prepared in Example 3) and LDH@NAF / H-PBMSA (prepared in Example 6); b is the differential scanning calorimetry (DSC) spectra of four coating films of H-PBMSA (prepared in Example 1), LDH / H-PBMSA (prepared in Example 2), NAF / H-PBMSA (prepared in Example 3) and LDH@NAF / H-PBMSA (prepared in Example 6); Figure 5 The contact angles of four coating films to water in air are H-PBMSA (prepared in Example 1), LDH / H-PBMSA (prepared in Example 2), NAF / H-PBMSA (prepared in Example 3) and LDH@NAF / H-PBMSA (prepared in Example 6). Figure 5 a) and the water absorption rate of the coating film ( Figure 5 b); Figure 6 In order to compare the surface gloss and flatness of sheepskin coated with different samples, the H-PBMSA prepared in Example 1 was coated on the sheepskin at a temperature of 12 mg / cm 2 The NAF / H-PBMSA finishing agent prepared in Example 3 was sprayed on sheepskin at 12 mg / cm 2 The LDH / H-PBMSA finishing agent prepared in Example 2 was sprayed on sheepskin at 12 mg / cm 2 The amount of spraying was 12 mg / cm on the sheepskin. 2 The leather was sprayed with an amount of , the leather sample after the sheepskin was coated with H-PBMSA prepared in Example 1 was recorded as P / L, the leather sample after the sheepskin was coated with LDH / H-PBMSA prepared in Example 2 was recorded as LDH / P / L, the leather sample after the sheepskin was coated with NAF / H-PBMSA prepared in Example 3 was recorded as NAF / P / L, and the leather sample after the sheepskin was coated with LDH@NAF / H-PBMSA prepared in Example 6 was recorded as LDH@NAF / P / L; Figure 7 In order to characterize the coating adhesion of sheepskin leather samples coated with different samples by the cross-hatch method, a, b, c, and d correspond to the H-PBMSA prepared in Example 1 on the sheepskin at 12 mg / cm 2 The NAF / H-PBMSA finishing agent prepared in Example 3 was sprayed on sheepskin at 12 mg / cm 2The LDH / H-PBMSA finishing agent prepared in Example 2 was sprayed on sheepskin at 12 mg / cm 2 The amount of spraying was 12 mg / cm on the sheepskin. 2 The leather is sprayed with a certain amount of paint; a', b', c', d' correspond to the leather samples a, b, c, d after being torn with a special tape; Figure 8 Middle: a is the stress-strain curve of H-PBMSA, LDH / H-PBMSA, NAF / H-PBMSA and LDH@NAF / H-PBMSA (prepared in Example 6) coating films; b is the stress-strain curve of LDH@NAF / H-PBMSA coating films prepared by adding different contents of LDH@NAF composite nanoparticles; Fig. 9 Figures 2 and 3 are the states of different coating films before combustion and after combustion for 10 s. a~d are the states of H-PBMSA, NAF / H-PBMSA, LDH / H-PBMSA and LDH@NAF / H-PBMSA (prepared in Example 6) coating films at the beginning of combustion, and a'~d' correspond to the states of a~d after combustion for 10 s. Fig.10 The coatings of uncoated raw leather, H-PBMSA (prepared in Example 1), LDH / H-PBMSA (prepared in Example 2), NAF / H-PBMSA (prepared in Example 3) and LDH@NAF / H-PBMSA (prepared in Example 6) were applied on sheepskin at a concentration of 12 mg / cm 2 The thermal conductivity of the coated leather after spraying was compared, which were recorded as Leather and P / L, LDH / P / L, NAF / P / L, and LDH@NAF / P / L; Fig.11 The unworn leather surface and the wear marks after spraying sheepskin with four finishing agents: H-PBMSA (prepared in Example 1), LDH / H-PBMSA (prepared in Example 2), NAF / H-PBMSA (prepared in Example 3) and LDH@NAF / H-PBMSA (prepared in Example 6). The coating surfaces observed under an optical microscope before and after wear were compared. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described in detail below in conjunction with specific examples, but the protection scope of the present invention is not limited thereto. In the following examples, the initiator aqueous solution is prepared by dissolving 0.280 g of APS in 21 mL of distilled water.
[0018] 1. Preparation of Nano-aramid Fibers Weigh 1 g of aramid (K-1313, provided by Zhengzhou Junshuo Biotechnology Co., Ltd.) and mix with 500 mL of dimethyl sulfoxide (DMSO) and repeatedly ultrasonically stir to make it uniformly dispersed, then add 0.1 g / mL potassium hydroxide aqueous solution (1.2 g potassium hydroxide dissolved in 12 mL of distilled water), react at 30-50 ° C for 7-8 days under magnetic stirring in a reaction bottle, end the reaction, add 2500 mL of deionized water and stir for 1-2 hours, filter to obtain solid, vacuum dry at 60 ° C, fully grind to obtain nano aramid fiber (referred to as NAF), and set aside. Nano aramid fiber has good dispersibility in water.
[0019] 2. Preparation of Nano-LDH 4.093 g (30 mmol) zinc chloride (ZnCl2) and 1.352 g (10 mmol) aluminum chloride (AlCl3) were dissolved in 50 mL distilled water and ultrasonically treated to obtain a mixed salt solution a; 3.623 g (90.6 mmol) NaOH and 0.52 g (4.9 mmol) anhydrous Na2CO3 were dissolved in 30 mL distilled water and ultrasonically treated to obtain a mixed alkali solution b; the b solution was dropped into the continuously stirred a solution to make the pH of the mixed solution between 11 and 13, and then the mixed solution was ultrasonically treated for 3 min, stirred for 5 min, and repeated three times, and then heated to 80°C in a water bath and refluxed for 2 to 3 h, and finally transferred to a 100 mL reactor and reacted at 110 to 120°C for 12 h, the reaction was terminated, and centrifuged (8000 r / min), the solid product was fully washed with distilled water until neutral, and vacuum dried at 60°C to obtain nano-hydrotalcite, recorded as LDH, for standby use. The prepared nano hydrotalcite has good dispersibility in water.
[0020] 3. Preparation of Nano-hydrotalcite@Aramid Fiber Composite (LDH@NAF) Weigh 1 g of aramid (K-1313, provided by Zhengzhou Junshuo Biotechnology Co., Ltd.) and mix it with 500 mL of dimethyl sulfoxide (DMSO) and repeatedly ultrasonically stir it to make it evenly dispersed. Then, add 12 mL of 0.1 g / mL potassium hydroxide aqueous solution (1.2 g KOH dissolved in 12 mL of distilled water) to the above mixture, transfer it to a reaction bottle, and stir it magnetically at 30-50 ° C for 7-8 days. End the reaction, add 2500 mL of distilled water and continue stirring for 1-2 h. Take 90 mL of the above reaction solution (NAF content is about 0.030 g) and keep stirring. At the same time, add 20 mL of an aqueous solution containing 0.713 g zinc chloride (ZnCl2, 5.2 mmol) and 0.231 g aluminum chloride (AlCl3, 1.73 mmol) and 20 mL of an aqueous solution containing 0.720 g sodium hydroxide (NaOH, 18 mmol). After the addition is complete, react at 80 ° C for 2-3 hours under stirring. h, and then transferred to a hydrothermal reactor for further hydrothermal reaction at 110-120 °C for 12 h. After the reaction was terminated, the solid precipitate was centrifuged at 8000 r / min. The solid product was washed and dried in vacuo at 60 °C to obtain a nano-hydrotalcite@aramid fiber composite, which was recorded as LDH@NAF and set aside.
[0021] Example 1 Weigh 0.736 g (7 mmol) HAM, 0.312 g (3.7 mmol) NaHCO3, 0.206 g (1 mmol) SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g (33.3 mmol) BA, 3.337 g (33.4 mmol) MMA and 0.164 g (2.3 mmol) AA thereto and stir evenly, then emulsify at 10000 rmp for 6 min using a Fluor FA25 shear emulsifier to form a pre-emulsified monomer I for later use; weigh 0.409 g SSS (2 mmol) and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g (66.6 mmol) BA, 6.663 g (66.6 mmol) MMA and 0.327 g (4.5 mmol) AA thereto and stir evenly, then emulsify at 10000 rmp using a Fluor FA25 shear emulsifier to form a pre-emulsified monomer I for later use; rmp for 6 min to form pre-emulsified monomer II for use; add pre-emulsified monomer I into a 250 mL three-necked flask with a condenser, mechanical stirring and thermometer, and when the temperature is raised to 40°C under strong stirring, slowly add 7 mL of initiator aqueous solution (prepared by dissolving 0.280 g APS in 21 mL distilled water, the same below), and after the addition is complete, heat the reaction to 80°C for 1 h, and then slowly add pre-emulsified monomer II and the remaining 14 mL of initiator aqueous solution to the emulsion, and finish dropping in about 1 h. After the addition is complete, continue to react for 6 h to obtain a multi-crosslinked copolymer, recorded as H-PBMSA (solid content 20wt%), which is set aside.
[0022] Example 2 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer I for standby use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer II for standby use; add pre-emulsified monomer I into a 250 ℃ condenser with a condenser, a mechanical stirrer and a thermometer. In a mL three-necked flask, when the temperature is raised to 40°C under strong stirring, 7 mL of initiator aqueous solution (prepared by dissolving 0.280 g APS in 21 mL distilled water, the same below) is slowly added dropwise. After the addition is complete, the temperature is raised to 80°C for reaction for 1 hour. Then, pre-emulsified monomer II and 14 mL of initiator aqueous solution are slowly added dropwise to the emulsion at the same time. The addition is completed in about 1 hour. After the addition is completed, the reaction is continued for 6 hours to obtain a multi-crosslinked copolymer, which is recorded as H-PBMSA and set aside. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add 2-3 drops of commercial concentrated ammonia (the same below) to adjust the pH to 7-8 and stir continuously, record it as emulsion ① for later use; weigh 0.04 g of nano-hydrotalcite dispersed in 5 mL of distilled water and continuously ultrasonically stir to make it evenly dispersed, then slowly drop the hydrotalcite dispersion into emulsion ①, stir for 1-2 h to make it evenly dispersed, and obtain nano-hydrotalcite / cross-linked copolymer composite emulsion, record it as LDH / H-PBMSA, and set aside.
[0023] Example 3 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer I for standby use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer II for standby use; add pre-emulsified monomer I into a 250 ℃ condenser with a condenser, a mechanical stirrer and a thermometer. In a 50 mL three-necked flask, when the temperature is raised to 40 °C under strong stirring, 7 mL of initiator aqueous solution (prepared by dissolving 0.280 g APS in 21 mL distilled water, the same below) is slowly added. After the addition is completed, the temperature is raised to 80 °C for 1 h. Then, the pre-emulsified monomer II and 14 mL of initiator aqueous solution are slowly added to the emulsion at the same time. The dripping is completed in about 1 h. After the dripping is completed, the reaction is continued for 6 h to obtain a multi-crosslinked copolymer, which is recorded as H-PBMSA and is set aside. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add ammonia water to adjust the pH to 7-8 and stir continuously, which is recorded as emulsion ① for use; weigh 0.04 g of nano-aramid fiber (NAF) and disperse it in 5 mL distilled water and stir it continuously to make it dispersed evenly, then slowly drip the hydrotalcite dispersion into emulsion ① and stir it for 1-2 h to make it dispersed evenly, to obtain a nano-aramid fiber / cross-linked copolymer composite emulsion, which is recorded as NAF / H-PBMSA and is set aside.
[0024] Example 4 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then use Fluke FA25 shear emulsifier at 10000 rmp for 6 min to form pre-emulsified monomer I for standby use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then use Fluke FA25 shear emulsifier at 10000 rmp for 6 min to form pre-emulsified monomer II for standby use; add pre-emulsified monomer I to a 250 ℃ condenser with a condenser, a mechanical stirrer and a thermometer; In a 50 mL three-necked flask, when the temperature is raised to 40 °C under strong stirring, 7 mL of initiator aqueous solution (prepared by dissolving 0.280 g APS in 21 mL distilled water, the same below) is slowly added. After the addition is completed, the temperature is raised to 80 °C for 1 h. Then, the pre-emulsified monomer II and 14 mL of initiator aqueous solution are slowly added to the emulsion at the same time. The dripping is completed in about 1 h. After the dripping is completed, the reaction is continued for 6 h to obtain a multi-crosslinked copolymer, which is recorded as H-PBMSA and is set aside. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add ammonia water to adjust the pH to 7-8 and stir continuously, which is recorded as emulsion ① for use; weigh 0.004 g of LDH@NAF and disperse it in 5 mL distilled water and stir it continuously to make it dispersed evenly. Then, the dispersion is slowly dropped into emulsion ① and stirred for 1-2 h to make it dispersed evenly. Nano-hydrotalcite@aramid fiber / cross-linked copolymer composite emulsion is obtained, which is recorded as 0.1%LDH@NAF / H-PBMSA and is set aside.
[0025] Example 5 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then use Fluke FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer I for standby use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then use Fluke FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer II for standby use; add pre-emulsified monomer I to a 250 ℃ condenser with a condenser, a mechanical stirrer and a thermometer. mL three-necked flask, under strong stirring, when the temperature is raised to 40℃, 7 mL of initiator aqueous solution (0.280 g APS dissolved in 21 mL distilled water, the same below) is slowly added dropwise, after the addition is complete, the temperature is raised to 80℃ for 1h, and then the pre-emulsified monomer II and 14 mL of initiator aqueous solution are slowly added dropwise to the emulsion at the same time, and the dripping is completed in about 1h, and the reaction is continued for 6h after the dripping is completed to obtain a multi-crosslinked copolymer, which is recorded as H-PBMSA and is set aside. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add ammonia water to adjust the pH to 7~8 and stir continuously, which is recorded as emulsion ① for standby; weigh 0.020 g LDH@NAF and disperse it in 5 mL distilled water and stir it continuously to make it dispersed evenly, then slowly drip the dispersion into emulsion ①, stir for 1~2h to make it completely dispersed evenly, and obtain nano-hydrotalcite@aramid fiber / crosslinked copolymer composite emulsion, which is recorded as 0.5%LDH@NAF / H-PBMSA and is set aside.
[0026] Example 6 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer I for use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer II for use; add pre-emulsified monomer I to a 250 ℃ condenser with a condenser, a mechanical stirrer and a thermometer. mL three-necked flask, under strong stirring, when the temperature is raised to 40℃, 7 mL of initiator aqueous solution (0.280 g APS dissolved in 21 mL distilled water, the same below) is slowly added, and after the addition is completed, the temperature is raised to 80℃ for 1h, and then the pre-emulsified monomer II and 14 mL of initiator aqueous solution are slowly added to the emulsion at the same time, and the dripping is completed in about 1h. After the dripping is completed, the reaction is continued for 6h to obtain a multi-crosslinked copolymer, which is recorded as H-PBMSA and set aside. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add ammonia water to adjust the pH to 7~8 and stir continuously, which is recorded as emulsion ① for use; weigh 0.040 g LDH@NAF and disperse it in 5 mL distilled water and stir it continuously to make it dispersed evenly, then slowly drip the dispersion into emulsion ①, stir for 1~2h to make it completely dispersed, and obtain nano-hydrotalcite@aramid fiber / crosslinked copolymer composite emulsion, which is recorded as 1%LDH@NAF / H-PBMSA and set aside.
[0027] Example 7 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then emulsify at 10000 rpm for 6 min using a Fluor FA25 shearing emulsifier to form a pre-emulsified monomer I for later use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then emulsify at 10000 rpm for 6 min using a Fluor FA25 shearing emulsifier min to form pre-emulsified monomer II for later use; add pre-emulsified monomer I into a 250mL three-necked flask equipped with a condenser, mechanical stirring and a thermometer, and when the temperature is raised to 40°C under strong stirring, slowly add 7mL of initiator aqueous solution (prepared by dissolving 0.280g APS in 21mL distilled water, the same below), and after the addition is complete, heat the reaction to 80°C for 1h, and then slowly add pre-emulsified monomer II and 14mL of initiator aqueous solution to the emulsion at the same time, and finish the addition in about 1h. After the addition is complete, continue the reaction for 6h to obtain a multi-crosslinked copolymer, recorded as H-PBMSA, for later use. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add ammonia water to adjust the pH to 7-8 and stir continuously, record it as emulsion ① for later use; weigh 0.060 g of LDH@NAF and disperse it in 5 mL of distilled water and stir it continuously by ultrasonic stirring to make it evenly dispersed, then slowly drop the dispersion into emulsion ① and stir for 1-2 h to make it completely dispersed, to obtain nano-hydrotalcite@aramid fiber / cross-linked copolymer composite emulsion, record it as 1.5%LDH@NAF / H-PBMSA, and set aside.
[0028] Example 8 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer I for standby use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then use Fluor FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer II for standby use; add pre-emulsified monomer I to a 250 ℃ condenser with a condenser, a mechanical stirrer and a thermometer. mL three-necked flask, under strong stirring, when the temperature is raised to 40℃, 7 mL of initiator aqueous solution (0.280 g APS dissolved in 21 mL distilled water, the same below) is slowly added dropwise, after the addition is complete, the temperature is raised to 80℃ for 1h, and then the pre-emulsified monomer II and 14 mL of initiator aqueous solution are slowly added dropwise to the emulsion at the same time, and the dripping is completed in about 1h, and the reaction is continued for 6h after the dripping is completed to obtain a multi-crosslinked copolymer, which is recorded as H-PBMSA and is set aside. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add ammonia water to adjust the pH to 7~8 and stir continuously, which is recorded as emulsion ① for standby; weigh 0.080 g LDH@NAF and disperse it in 5 mL distilled water and stir it continuously to make it dispersed evenly, then slowly drip the dispersion into emulsion ①, stir for 1~2h to make it completely dispersed evenly, and obtain nano-hydrotalcite@aramid fiber / crosslinked copolymer composite emulsion, which is recorded as 2%LDH@NAF / H-PBMSA and is set aside.
[0029] Example 9 Weigh 0.736 g HAM, 0.312 g NaHCO3, 0.206 g SSS and 30 mL H2O and ultrasonically treat for 3 min until completely dissolved, add 4.272 g BA, 3.337 g MMA and 0.164 g AA thereto and stir evenly, then use Fluke FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer I for standby use; weigh 0.409 g SSS and add it to 40 mL distilled water and stir until completely dissolved, add 8.528 g BA, 6.663 g MMA and 0.327 g AA thereto and stir evenly, then use Fluke FA25 shear emulsifier at 10000 rpm for 6 min to form pre-emulsified monomer II for standby use; add pre-emulsified monomer I to a 250 ℃ condenser with a condenser, a mechanical stirrer and a thermometer. In a 50 mL three-necked flask, when the temperature is raised to 40 °C under strong stirring, 7 mL of initiator aqueous solution (prepared by dissolving 0.280 g APS in 21 mL distilled water, the same below) is slowly added. After the addition is completed, the temperature is raised to 80 °C for 1 h. Then, the pre-emulsified monomer II and 14 mL of initiator aqueous solution are slowly added to the emulsion at the same time. The dripping is completed in about 1 h. After the dripping is completed, the reaction is continued for 6 h to obtain a multi-crosslinked copolymer, which is recorded as H-PBMSA and is set aside. Weigh 20 g of H-PBMSA emulsion in a 50 mL beaker, add ammonia water to adjust the pH to 7-8 and stir continuously, which is recorded as emulsion ① for use; weigh 0.100 g of LDH@NAF and disperse it in 5 mL distilled water and stir it continuously to make it dispersed evenly. Then, the dispersion is slowly dropped into emulsion ① and stirred for 1-2 h to make it completely dispersed evenly. Nano-hydrotalcite@aramid fiber / cross-linked copolymer composite emulsion is obtained, which is recorded as 2.5%LDH@NAF / H-PBMSA and is set aside.
[0030] The infrared spectra of LDH, the cross-linked copolymer (H-PBMSA) prepared in Example 1, and the LDH@NAF / H-PBMSA nanocomposite prepared in Example 6 were compared. Figure 1 It can be seen that LDH@NAF / H-PBMSA was successfully prepared.
[0031] UV-759S UV spectrophotometer was used to test the UV-visible absorption spectra of pure cross-linked copolymer coating films and different nanocomposite coating films. Figure 2As shown in a, H-PBMSA, LDH / H-PBMSA, NAF / H-PBMSA and LDH@NAF / PBMSA correspond to the UV-visible spectra of the coating agents prepared in Example 1, Example 2, Example 3 and Example 6, respectively, wherein illustrations ① to ④ correspond to the photos of the coating agents prepared in Example 1, Example 2, Example 3 and Example 6 formed on a glass sheet using a coating machine. Figure 2 As can be seen in a, the addition of nanofillers enhances the UV shielding performance of the coating film, while having almost no effect on the transparency of the coating film.
[0032] Figure 2 b is a UV-visible absorption spectrum of LDH@NAF / H-PBMSA coating films prepared by adding different contents of LDH@NAF composite nanoparticles at 250-800 nm and a film-forming picture on a glass sheet, wherein 0%, 0.1%, 0.5%, 1%, 1.5%, 2% and 2.5% are prepared by Example 1, Example 4, Example 5, Example 6, Example 7, Example 8 and Example 9, respectively. It can be seen from the figure that when the content of LDH@NAF composite nanoparticles exceeds 1%, the transparency of the film is affected, and when the LDH@NAF filler is 1%, it has better UV shielding performance; Figure 8 b Stress-strain curves of LDH@NAF / H-PBMSA coating films prepared by adding different contents of LDH@NAF composite nanoparticles, where 0%, 0.1%, 0.5%, 1%, 1.5%, 2% and 2.5% are prepared by Example 1, Example 4, Example 5, Example 6, Example 7, Example 8 and Example 9, respectively. It can be seen from the figure that when the content of LDH@NAF composite nanoparticles is 1%, the elongation at break of the coating film is the largest and the toughness is the best. In summary, the comprehensive performance of the LDH@NAF / H-PBMSA coating film is the best when the filler is added at 1%.
[0033] The morphology of the prepared nano-hydrotalcite, aramid fiber and LDH@NAF was observed under a scanning electron microscope (SEM). Figure 3 ,from Figure 3 It can be seen that the diameter of the nano-hydrotalcite sheet is about 450 nm and the thickness is about 50 nm. After composite, the hydrotalcite nano-sheets crystallize and grow evenly on the surface of the aramid fiber.
[0034] The thermal properties of different coating film samples were tested using a TGA / DSC 3+ thermogravimetric analyzer and a DSC250 differential scanning calorimeter. Figure 4a (curve H-PBMS corresponds to the product prepared in Example 1, curve LDH / H-PBMSA corresponds to the product prepared in Example 2, curve NAF / H-PBMSA corresponds to the product prepared in Example 3, and curve LDH@NAF / H-PBMSA corresponds to the product prepared in Example 6) It can be seen that the maximum thermal decomposition temperature (399.5°C) of the NAF / / H-PBMSA coating film is higher than that of other coating films, indicating that the addition of NAF may further improve the thermal stability of the nanocomposite coating film. Figure 4 b is the DSC change curve of different coating films (curve H-PBMS corresponds to the product prepared in Example 1, curve LDH / H-PBMSA corresponds to the product prepared in Example 2, curve NAF / H-PBMSA corresponds to the product prepared in Example 3, and curve LDH@NAF / H-PBMSA corresponds to the product prepared in Example 6) at -60~70°C, which further proves the successful preparation of the target product. The glass transition temperature (0.22°C) of the LDH@NAF / H-PBMSA coating film is significantly lower than the glass transition temperature (3.87°C) of the pure cross-linked polymer H-PBMSA, which broadens the use temperature range of the coating agent. In comparison, the thermal stability and weather resistance of the LDH@NAF / H-PBMSA nanocomposite coating are better.
[0035] The contact angle test results of H-PBMSA coating film and different nanocomposite coating films (thickness of 0.4~0.5 mm) to water in air are shown in Figure 5 a, it can be seen that the introduction of LDH@NAF can improve the hydrophobicity of the coating film, so that the contact angle of the coating film to water increases from 90.9° to 102.1°; the water absorption rate of the H-PBMSA coating film and different nanocomposite coating films is as follows Figure 5 b and Table 1, it can be seen that the water absorption rate of the membrane is reduced from 33.4% of the pure polymer to 21.6% due to the interfacial synergistic effect produced by the composite of LDH and NAF.
[0036] Comparison of the glossiness and flatness of the sheepskin surface coated with different samples. The H-PBMSA coating agent prepared in Example 1, the NAF / H-PBMSA coating agent prepared in Example 3, the LDH / H-PBMSA coating agent prepared in Example 2, and the LDH@NAF / H-PBMSA coating agent prepared in Example 6 were all coated on the sheepskin at a temperature of 12 mg / cm 2The leather sample after spraying with an amount of , the leather sample after the sheepskin is coated with H-PBMSA prepared in Example 1 is recorded as P / L, the leather sample after the sheepskin is coated with LDH / H-PBMSA prepared in Example 2 is recorded as LDH / P / L, the leather sample after the sheepskin is coated with NAF / H-PBMSA prepared in Example 3 is recorded as NAF / P / L, and the leather sample after the sheepskin is coated with LDH@NAF / H-PBMSA prepared in Example 6 is recorded as LDH@NAF / P / L, from Figure 6 It can be clearly seen that the leather sample coated with LDH@NAF / H-PBMSA composite coating agent is more glossy.
[0037] The cross-hatch method was used to test the coating adhesion of different coating films. The results are shown in Figure 7 and Table 2, from Figure 7 (a, b, c, and d in the figure correspond to the H-PBMSA finishing agent prepared in Example 1 on sheepskin at 12 mg / cm 2 The NAF / H-PBMSA finishing agent prepared in Example 3 was sprayed on the sheepskin at 12 mg / cm 2 The LDH / H-PBMSA finishing agent prepared in Example 2 was sprayed on the sheepskin at 12 mg / cm 2 The LDH@NAF / H-PBMSA finishing agent prepared in Example 6 was sprayed on the sheepskin at 12 mg / cm 2 The coated leather after spraying with a certain amount of coating; a', b', c', d' correspond to the leather samples a, b, c, d after being torn off with special tape. It can be seen that the adhesion rating of the coating of LDH@NAF / H-PBMSA composite coating agent is 0, which is significantly better than the rating of 1 of pure polymer.
[0038] Take 20mL of H-PBMSA pure copolymer emulsion prepared in Example 1, LDH / H-PBMSA nanocomposite emulsion prepared in Example 2, NAF / H-PBMSA nanocomposite emulsion prepared in Example 3, and LDH@NAF / H-PBMSA nanocomposite emulsion prepared in Example 6, and pour them into 5×13 cm glass molds respectively, dry them naturally at room temperature for 48 h, and then place them in a vacuum drying oven for drying for 24 h (film thickness after drying is 0.4~0.5 mm), and cut them into dumbbell-shaped splines according to the shapes specified in the national standard GB / T 528-2009 for tensile stress-strain properties of thermoplastic rubber for use. Use TCS-2000 microcomputer-controlled electronic universal testing machine to test the stress-strain characteristics of different coatings, with a tensile speed of 500 mm / min. The specific results are shown in Figure 8 a. As can be seen from the figure, the introduction of LDH@NAF increases the strength of the nanocomposite coating to about 11.3 MPa.
[0039] The H-PBMSA coating film prepared in Example 1, the NAF / H-PBMSA coating film prepared in Example 3, the LDH / H-PBMSA coating film prepared in Example 2, and the LDH@NAF / H-PBMSA coating film prepared in Example 6 were cut into 1 cm×2 cm sizes with a thickness of 0.4-0.5 mm, and ignited to observe the combustion conditions before and after 10 s. Fig. 9 It can be seen that the combustion rate of the nanocomposite coating film with the addition of LDH and LDH@NAF is significantly reduced, and the LDH@NAF / H-PBMSA composite coating film can delay the combustion rate.
[0040] The thermal conductivity of copolymer H-PBMSA and different nanocomposite coating agents on sheepskin was tested on a TC3000 thermal conductivity meter at 12 mg / cm 2 The thermal conductivity of the finished leather obtained after spraying is shown in the test results. Fig.10 Compared with H-PBMSA coated leather and uncoated leather, the thermal conductivity of LDH@NAF / H-PBMSA coated leather dropped to 0.073 W / (m·k). LDH@NAF / H-PBMSA can improve the thermal insulation performance of sheepskin.
[0041] The wear test was conducted by first spraying the samples (the spraying amount of different finishing agents on sheepskin was 12 mg / cm 2 , the leather sample after coating sheepskin with H-PBMSA prepared in Example 1 is recorded as P / L, the leather sample after coating sheepskin with LDH / H-PBMSA prepared in Example 2 is recorded as LDH / P / L, the leather sample after coating sheepskin with NAF / H-PBMSA prepared in Example 3 is recorded as NAF / P / L, and the leather sample after coating sheepskin with LDH@NAF / H-PBMSA prepared in Example 6 is recorded as LDH@NAF / P / L, ) is placed facing the sandpaper, and a 100 g weight is placed on top of the sample. Then, move 10 cm in one direction and another 10 cm in the opposite direction. The whole process is called a wear cycle, and the number of cycles is 10. The wear marks on the leather surface after coating with pure multi-cross-linked copolymers and different nanocomposite coating agents are observed using an RTS2 type microfluorescence spectrometer to compare the wear resistance of the samples. From Fig.11 It can be seen that the leather coated with the pure polymer coating agent without adding nanoparticles (prepared in Example 1) has obvious scratches, and the leather sample coated with the LDH@NAF / H-PBMSA nanocomposite coating agent prepared in Example 6 shows only very few scratches after wear, indicating that the synergistic effect of nano-hydrotalcite and aramid fiber can significantly improve the wear resistance of the coated leather.
[0042] The water absorption rate of the sample is tested and calculated as follows: three pieces of the same sample are taken, each with a size of 3×3 cm, and their masses are weighed respectively. The initial mass is recorded as M0. The weighed samples are marked and placed in a petri dish filled with water. They are left to soak for 24 hours. Then the soaked samples are taken out and the surface water is dried and weighed. The water absorption rate W of the sample is calculated as follows: The average value of the three test results is taken as the water absorption rate of the sample. The results are shown in Table 1.
[0043] Table 1 Comparison of water absorption of different coating films From the data in Table 1, it can be seen that compared with the pure cross-linked copolymer H-PBMSA, the water absorption of different nanocomposite coating films is reduced, and the LDH@NAF / H-PBMSA nanocomposite coating film has better water resistance.
[0044] Table 2 Rating of coating adhesion of sheepskin after finishing according to national standard GB / T9286-88 From the data in Table 2, it can be seen that compared with pure polymer H-PBMSA, the adhesion of LDH@NAF / H-PBMSA nanocomposite coating to sheepskin is significantly improved.
Claims
1. A method for preparing a nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent, characterized in that: The steps include: (1) N-hydroxymethyl acrylamide, sodium bicarbonate and sodium p-styrene sulfonate are dissolved in water, and then butyl acrylate, methyl methacrylate and acrylic acid are added for pre-emulsification to obtain pre-emulsified monomer I; butyl acrylate, methyl methacrylate, sodium p-styrene sulfonate and acrylic acid are mixed with water for emulsification to obtain pre-emulsified monomer II; the pre-emulsified monomer is heated to 40-50° C. under stirring to obtain reaction solution ①, an initiator aqueous solution is added dropwise to the reaction solution ①, and then the temperature is increased to 75-85° C. for reaction for 0.5-1 h to obtain reaction solution ②, and then the pre-emulsified monomer II and the remaining initiator aqueous solution are added dropwise to the reaction solution ② to continue the reaction for 4-7 h to obtain the target product cross-linked copolymer, which is recorded as H-PBMSA emulsion; (2) Under stirring, a mixed aqueous solution of zinc chloride and aluminum chloride and an aqueous solution of sodium hydroxide were simultaneously added dropwise to the dispersion of nano-aramid fiber. After the addition was completed, the mixture was stirred at 75-85°C for 2-3 h, and then transferred to a hydrothermal reactor for hydrothermal reaction at 110-120°C for 10-20 h. After the reaction was terminated, the mixture was centrifuged, and the solid product was washed and dried to obtain a nano-hydrotalcite@aramid fiber composite product, which was recorded as LDH@NAF and set aside. (3) Disperse LDH@NAF evenly in water to obtain dispersion A. Take H-PBMSA emulsion and adjust its pH to 7-8 under stirring. Add dispersion A dropwise into H-PBMSA and stir for 1-2 h to obtain nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent, recorded as LDH@NAF / H-PBMSA.
2. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 1, characterized in that: In the step (1), the molar ratio of each monomer in the pre-emulsified monomer I is: butyl acrylate: methyl methacrylate: sodium p-styrene sulfonate: acrylic acid: N-hydroxymethyl acrylamide = (33-34): (33-34): 1: (2-3): (3-4); the molar ratio of each monomer in the pre-emulsified monomer II is: butyl acrylate: methyl methacrylate: sodium p-styrene sulfonate: acrylic acid = (33-34): (33-34): 1: (2-3), and the amount of sodium bicarbonate added is 50-90% of the total molar amount of acrylic acid in the pre-emulsified monomer I and the pre-emulsified monomer II.
3. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 1, characterized in that: The preparation process of the nano-aramid fiber dispersion in step (2) is as follows: aramid is uniformly dispersed in dimethyl sulfoxide, followed by adding 0.05-0.2 g / mL potassium hydroxide aqueous solution, stirring and reacting at 30° C.-50° C. for 7-8 days, ending the reaction, and adding deionized water and stirring for 1-2 h.
4. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 3, characterized in that: Every 1 g of aramid needs to be dissolved in 400~600 mL of dimethyl sulfoxide, and every 1 g of aramid needs to be added with 10~15 mL of 0.05~0.2 g / mL potassium hydroxide aqueous solution.
5. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 1, characterized in that: In the step (1), the total mass of the pre-emulsified monomer I accounts for 33-35% of the total amount of monomers added.
6. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 1, characterized in that: In the step (1), the initiator is ammonium persulfate, the concentration of the initiator aqueous solution is 0.01-0.02 g / mL, and the amount of the initiator added is 1-1.5% of the total mass of butyl acrylate, methyl methacrylate, acrylic acid monomer, N-hydroxymethyl acrylamide and sodium p-styrene sulfonate, wherein the amount of the initiator added to the pre-emulsified monomer I is 30-40% of the total amount of the initiator.
7. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 1, characterized in that: In the step (2), the molar ratio of zinc chloride, aluminum chloride and sodium hydroxide is 3:1:(9-12), the amount of nano-aramid fiber added is 3-4% of the total mass of zinc chloride and aluminum chloride, the concentration of zinc chloride in the mixed aqueous solution of zinc chloride and aluminum chloride is 0.2-0.3 mmol / mL, and the concentration of the sodium hydroxide aqueous solution is 0.8-1 mmol / mL.
8. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 1, characterized in that: In the step (3), the amount of LDH@NAF added to the cross-linked copolymer matrix accounts for 0.1-2.5% of the effective amount of the polymer.
9. The method for preparing the nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent according to claim 1, characterized in that: In step (3), ammonia water is used to adjust the pH to 7-8, and 0.004 g-0.100 g of LDH@NAF is dispersed in 5 mL of distilled water.
10. A nano-hydrotalcite@aramid fiber / cross-linked copolymer composite leather finishing agent prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of layered doubled hydroxide modified polyacrylate composite emulsion
CN105801748A
Preparation method of multi-functional hydrotalcite / polymer nano-composite additive for leather
CN105949369A
Synthetic leather
CN111212944A
Surface-modified aramid fiber and preparation method therefor
WO2017190492A1